The Influence Of Tax Sanctions And Tax Services On Motor Vehicle Taxpayer Compliance At The Samsat Office Of Majene District - Muhammad Mukhram*; Wulan Ayuandiani (Universitas Syiah Kuala, 2023)
Tax is one of the sources of state revenue directed at national development in order to realize the welfare of all people in Indonesia. Paying motor vehicle tax to taxpayers is very important in supporting regional income in particular and national income in general. However, the realization of tax payments for motor vehicle taxpayers in the Majene Regency area has not been maximized. This can be seen from the arrears in motor vehicle tax payments that have fluctuated in quite large nominal amounts over the last 5 years. This study aims to determine how much influence tax sanctions and tax services have on motorized vehicle compliance at the Majene District Samsat Office. This study uses quantitative data analysis methods using econometric models , namely multiple linear regression analysis methods, with the help of SPSS Version 21 . The results of this study indicate that the tax penalty variable has no effect on taxpayer compliance as indicated by the t count (0.358) t table (1.984). Next , the variable tax sanctions on taxpayer compliance t count (2.291) t table (1.984), which means that tax services have a significant effect on taxpayer compliance in paying motor vehicle taxes. The simultaneous influence of tax sanctions and tax services on taxpayer compliance can be seen in the value F count F table , which is obtained 3.094 3.090, which means that tax sanctions and tax services simultaneously affect taxpayer compliance in paying motor vehicle taxes at the Majene District Samsat Office